Flood-Adaptive Planning Model for Mid-River Islands in Hanoi Based on Green Corridor and BGI Theory - Nguyen Van Tuyen; Dao Thi Nhu; Nguyen Thu Huong; Nguyen Hoai Thu (International Journal of Sustainable Construction Engineering and Technology, 2026)
Mid-river islands in the Red River hold significant ecological and cultural value but remain poorly integrated into Hanoi’s green infrastructure. This study addresses the gap by examining the current conditions of the largest mid-river island and proposing a flood-adaptive development model grounded in the Green Corridor framework. The methodology combines policy review, hydrological and elevation analysis using long-term official datasets, spatial assessment of morphological change, field surveys, and SWOT evaluation. Results indicate a trend toward greater geomorphological stability alongside major management challenges. Five thematic park zones are proposed using modular, non-permanent, and flood-resilient structures compliant with the Law on Dikes, contributing a scientifically grounded model for sustainable river-corridor planning.